Implementation of Islamic Religious Education Learning in Higher Education on The Pandemic Period - Siti Maryam Munjiat (Nazhruna: Jurnal Pendidikan Islam, 2020)
This study aims to explain and describe the implementation of PAI learning in higher Education institutions during the pandemic. This research method uses qualitative research with a case study approach and research design using analytical descriptives. The place of this research was at the KH Abdul Chalim Pacet Mojokerto Islamic Boarding School Institute during the pandemic from mid-March to May 2020. The results of the study: 1) online PAI learning planning should look at the condition of lecturers and students regarding the ability to conduct online lectures. Lecturers are given the freedom to conduct online lectures using any media as long as it is useful and learning outcomes can be maximized. 2) the implementation of PAI learning is carried out online through lecture and discussion methods. 3) Evaluation of PAI learning in Higher Education includes: a) student activity and discipline in carrying out learning b) assignments to students in the form of presentations, working on papers, c) midterm examinations d) written examinations, and assignments at the end of the semester.